Origin of polyoma virus-associated endonuclease. - Rouget, P (1976)
Polyoma virus particles purified from infected cells, but not from the culture medium, exhibited an endonuclease activity distinct from the serum contaminant recently described. This endonuclease cleaved form I polyoma DNA once only per molecule, at one of three possible sites corresponding to the known adenosine-ribosylthymine-rich regions of the molecule.